Performance Assessment of Gravity Retaining Wall with Rubber Tyre Waste mixed in dry cohesionless Backfill - Sadia Kantroo; Amit Srivastava; Alok Sharma (ASEAN Journal of Science and Engineering, 2022)
Rubber tyre waste is a huge burden on environmental system. In the present study, performance of gravity retaining wall system is assessed, both in deterministic and probabilistic framework, by utilizing rubber waste mix in the backfill. In the probabilistic approach, performance of a geotechnical system is measured in terms of an index popularly called “reliability index b”, a measure of probability of success of system. Concept of response surface methodology (RSM) has been applied to establish an approximate functional relationship between input geotechnical parameters, and output response, i.e. factor of safety through numerical analysis and then reliability index b is evaluated using FORM approach. Present study demonstrates the two aspects, i.e., by considering the case of a gravity retaining wall, i.e., reliability of computed value of factor of safety and role of mixing tyre chips in improving the performance of gravity wall system